Gambaran Tingkat Kecemasan pada Mahasiswa di Masa Pandemi COVID-19 - Walean, Clinton J. S.; Pali, Cicilia; Sinolungan, Jehosua S. V. (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: : COVID-19 has spread worldwide and become a global pandemic. This situation may pose psychological stress, including anxiety. In this situation, students are vulnerable to anxiety. Anxiety levels experienced by students differ from one to another. This study aimed to discover students' anxiety level illustration in countering the COVID-19 pandemic in various countries from each literature. This study was a literature review that searched data using three databases, i.e., Pubmed, ClinicalKey, and ScienceDirect. Keywords used were Anxiety AND College Students OR University Students AND COVID-19. The study found that of the total 25,984 students from all literature, 53% of students had no anxiety, 28.9% of students had mild anxiety, 10.7% of students had moderate anxiety, 6.6% of students had severe anxiety, and 0.8% students had very severe anxiety. The literature review results demonstrate that students could have anxiety during the COVID-19 pandemic era. Mild anxiety was the most prominent type that occurred in students, while severe anxiety was rare. Female students were more susceptible to anxiety during the COVID-19 pandemic era than male students. First-year and second-year students and also young adults students experiences anxiety more often. The predictors of anxiety are things related to the academic fields.Keywords: Anxiety, Students, COVID-19 Pandemic Abstrak: COVID-19 telah menyebar ke seluruh penjuru dunia dan telah menjadi global pandemic. Situasi ini dapat menyebabkan tekanan psikologis termasuk kecemasan. Pada situasi ini mahasiswa rentan mengalami kecemasan. Tingkatan kecemasan yang dialami oleh mahasiswa berbeda – beda setiap orang. Penelitian ini bertujuan untuk mengetahui gambaran tingkat kecemasan mahasiswa dalam menghadapi pandemi COVID-19 di berbagai negara dari setiap literatur. Penelitian ini merupakan penelitian berbentuk literature review dengan pencarian data menggunakan tiga database yakni Pubmed, ClinicalKey dan ScienceDirect. Kata kunci yang digunakan yaitu Anxiety AND College Students OR University Students AND Covid-19. Penelitian ini mendapatkan hasil bahwa dari 25.984 jumlah keseluruhan mahasiswa yang dijumlahkan dari setiap literatur, terdapat 53% mahasiswa tidak cemas, 28.9% mahasiswa cemas ringan, 10.7% mahasiswa cemas sedang, 6.6% mahasiswa cemas berat, 0.8% mahasiswa cemas sangat berat. Hasil penelitian literature review menunjukkan mahasiswa dapat mengalami kecemasan di masa pandemi COVID-19, kecemasan ringan adalah tingkat kecemasan yang paling sering dialami oleh mahasiswa sedangkan kecemasan berat sangat jarang dialami oleh mahasiswa. Mahasiswa perempuan lebih sering mengalami kecemasan di masa pandemi COVID-19 dibandingkan mahasiswa laki – laki. Mahasiswa tahun pertama dan tahun kedua juga mahasiswa di usia dewasa muda lebih sering mengalami kecemasan. Faktor-faktor penyebab kecemasan paling sering yaitu cemas terkait hal-hal bidang akademik mahasiswa.Kata Kunci: Kecemasan, Mahasiswa, COVID-19